2014
DOI: 10.1007/s11606-014-2956-0
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Discharge Instructions: Comprehension and Compliance Among Older Adults

Abstract: BACKGROUND: Little is known regarding the prevalence or risk factors for non-comprehension and noncompliance with discharge instructions among older adults. OBJECTIVE: To quantify the prevalence of noncomprehension and non-compliance with discharge instructions and to identify associated patient characteristics. RESEARCH DESIGN: Prospective cohort study. SUBJECTS: Four hundred and fifty adults aged ≥ 65 admitted to medical and surgical units of a tertiary care facility and meeting inclusion criteria. MEASURES:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 34 publications
2
50
1
Order By: Relevance
“…For example, a discussion with a younger, relatively uncomplicated patient may focus on secondary prevention and reduction of risk factors such as smoking, while a discussion with an older patient may focus on a constellation of co-occurring conditions and polypharmacy rather than on the patient’s heart condition. Additionally, non-comprehension of discharge instructions has been reported among elderly patients less than a week post-discharge[32]. Although women hospitalized with ACS tend to be older[33], we found that men were more likely to perceive their heart condition to be cured, independent of age.…”
Section: Discussionmentioning
confidence: 51%
“…For example, a discussion with a younger, relatively uncomplicated patient may focus on secondary prevention and reduction of risk factors such as smoking, while a discussion with an older patient may focus on a constellation of co-occurring conditions and polypharmacy rather than on the patient’s heart condition. Additionally, non-comprehension of discharge instructions has been reported among elderly patients less than a week post-discharge[32]. Although women hospitalized with ACS tend to be older[33], we found that men were more likely to perceive their heart condition to be cured, independent of age.…”
Section: Discussionmentioning
confidence: 51%
“…Some patients do not understand some of the information conveyed during discharge, including information about their medications [47], particularly for older patients [48,49]. For hospitals that are or will soon begin to implement preemptive PGx testing, providers and patients may benefit from a section on PGx testing in the discharge summary or a separate handout of the results.…”
Section: Overcoming Challenges To Communicating Pgx Test Resultsmentioning
confidence: 99%
“…Within hospitals, Albrecht et al 3 report that more than 25 % of patients do not understand their discharge…”
mentioning
confidence: 99%
“…Within hospitals, Albrecht et al 3 report that more than 25 % of patients do not understand their discharge medication instructions and 50 % do not understand the dietary instructions. With so many patients uninformed, it is unsurprising that hospital readmission rates show few signs of decline.…”
mentioning
confidence: 99%